2002
DOI: 10.1016/s0002-9440(10)64242-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Angiogenesis by Vascular Endothelial Growth Factor and Angiopoietin-1 in the Rat Aorta Model

Abstract: Vascular endothelial growth factor (VEGF) and angiopoietin-1 (Ang-1) promote the spontaneous angiogenic response of freshly cut rat aortic rings. When VEGF and Ang-1 were tested in cultures of 14-day-old rings, which are quiescent and unable to spontaneously produce neovessels, only VEGF was capable of inducing an angiogenic response. Ang-1 failed to initiate angiogenesis in this system, but significantly potentiated VEGF-induced neovessel sprouting. Potential differences in cell signaling triggered by VEGF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 32 publications
(41 reference statements)
1
26
0
Order By: Relevance
“…Because the inhibition of either the PI3/Akt/mTOR/S6K1 or STAT3 signaling resulted in almost complete suppression of 15(S)-HETE-induced angiogenesis, it is possible that these two signaling pathways play stage-specific events of angiogenesis. It was reported that PI3K/AKT signaling plays an important role in the sprouting of endothelial cells (46,47). On the other hand, VEGF is needed for the survival and maintenance of the plasticity of the vessel (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Because the inhibition of either the PI3/Akt/mTOR/S6K1 or STAT3 signaling resulted in almost complete suppression of 15(S)-HETE-induced angiogenesis, it is possible that these two signaling pathways play stage-specific events of angiogenesis. It was reported that PI3K/AKT signaling plays an important role in the sprouting of endothelial cells (46,47). On the other hand, VEGF is needed for the survival and maintenance of the plasticity of the vessel (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the MAPK pathway in tumor proliferation is well documented. Activation of the MAPK pathway occurs in response to integrin-mediated cellular adhesion to the extracellular matrix, which plays a critical role in both tumor metastasis and angiogenesis (Chen et al, 1998;Zhu et al, 2002). Previously, we have demonstrated that Figure 6 Inhibitory effect of green tea polyphenol on UVB-induced phosphorylation of p38 in SKH-1 hairless mice.…”
Section: Discussionmentioning
confidence: 99%
“…3,15 Aorta rings from age-matched WT, Het, and knockout (KO) mice were embedded in rat collagen I (2 mg/mL) and cultured with serum-free media (Invitrogen, No. 17601) and vascular endothelial cell growth factor (VEGF) (0, 2, 4, or 8 ng/mL, nϭ4 rings per dose).…”
Section: Aorta Explant Sprouting Assaymentioning
confidence: 99%
“…17601) and vascular endothelial cell growth factor (VEGF) (0, 2, 4, or 8 ng/mL, nϭ4 rings per dose). 3,15 We measured sprout area in images captured through a Nikon SMZ microscope (50ϫ magnification). Maximum sprout area was normalized to a valueϭ1.…”
Section: Aorta Explant Sprouting Assaymentioning
confidence: 99%